Systematic Review: Acupuncture vs Standard Pharmacological Therapy for Migraine Prevention - Zhang, Niushen; Houle, Tim; Hindiyeh, Nada; Aurora, Sheena K. (Headache, 2020)
Background Standard pharmacological treatment of migraine has many shortcomings. Acupuncture is becoming a more widely used therapy for the prevention and treatment of migraine, but its effectiveness is still in question when compared to the pharmacological treatments even though very few of these have Class A and B evidence for migraine prevention. This is a systematic review of data from existing randomized trials that compare the effectiveness of acupuncture treatment with conventional migraine preventative medications. Methods Custom‐designed strategy was used for searching Pubmed (includes MEDLINE), Scopus (includes EMBASE). The inclusion criteria were English language and randomized trials. No date restriction was utilized. We included randomized trials and randomized controlled trials in adult patients that compared the clinical effects of acupuncture with a standard migraine preventive medication in patients with a diagnosis of chronic or episodic migraine with or without aura. We excluded letters and studies on acupuncture for headaches other than migraine. Two reviewers checked eligibility; extracted information on patients, interventions, methods, and results; and assessed the quality of the acupuncture intervention based on the American Academy of Neurology Classification of evidence matrix for therapeutic trials. The present review was not registered. Results Out of the 706 search results, 7 clinical trials, with a total of 1430 participants, met inclusion criteria for trials comparing the effectiveness of acupuncture to standard pharmacologic treatment. Several of the studies showed acupuncture to be more effective than standard pharmacological treatments for migraine prevention; however, methodological heterogeneity precluded aggregation of these data. Conclusions There is growing evidence that acupuncture is just as effective and has fewer side effects than many of the standard pharmaceutical agents that are currently used. However, the heterogeneity of the existing studies limits the effective comparison and analysis.